Strategy Analysis of Sustainability of Small and Medium Enterprises (MSME’s) in Increasing Productivity and Profit in The Middle of Covid-19 Pandemic - Zalkha Soraya; Warda Warda; A. Nur Fitrianti; Rini Sulistiyanti; Andi Arifwangsa Adiningrat (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2022)
The purpose of this study is to investigate the impacts of Covid-19 on business productivity and MSME profits, as well as to establish the effectiveness of the MSME business continuity strategy in improving company productivity and MSME profits during the Covid-19 pandemic in Makassar City. This analysis uses a descriptive qualitative approach, analyzing MSME business continuity plans during the Covid-19 pandemic through a literature review. The processes included data analysis, reduction, presentation, and conclusion. The results showed that the Covid-19 pandemic had an impact on the productivity and profit of MSMEs due to reduced distribution of raw materials, decreased profits, and decreased sales. The MSME business continuity strategy for increasing business productivity is performed by keeping the environment clean during the Covid-19 pandemic and expanding work facilities to a value of 100%, which is classified as extremely effective, while the business continuity strategy is performed through creativity and innovation in the products produced, as well as the use of technology in marketing products, which achieves a value of 95%.